Obtención de la notificación sanitaria de queso fresco elaborado en el laboratorio de procesos de lácteos de la carrera de Agroindustria de la Universidad Técnica de Cotopaxi. - Casa Vilca, Rosario Elizabeth (2021)
The present research project was focused on obtaining the sanitary notification of fresh cheese made in the dairy processes’ laboratory of the Agroindustry career of the Technical University of Cotopaxi, in order to guarantee and support the commercialization of the products made by the associations linked to the service of the University. For the production process of the fresh cheese production, a technical diagram provided by the head of the laboratory was applied, which was used under the control of Good Manufacturing Practices (GMP). This process is focused on the monitoring and control of operating parameters both in raw material, product in process and finished product. For the analysis of fresh cheese, seven samples were sent in 125g presentations to a certified food analysis laboratory, in which the results obtained reflected that all the physical-chemical and microbiological parameters analyzed are within the standards established by the Ecuadorian Technical Standard INEN 1528. In order to evaluate the suitability conditions of the dairy process laboratory of the Technical University of Cotopaxi for the elaboration of products for food purposes, a comparative analysis was carried out with respect to the parameters established by Resolution 057 by the National Agency for Regulation, Control and Sanitary Surveillance (ARCSA). That result showed that 96% of the requirements of that current regulations are fulfilled. Finally, the compilation and corresponding presentation of the technical and legal requirements to obtain the sanitary notification was carried out. The operating license was categorized as an industry by the ARCSA, which generates a substantial difference in the payment of the fee compared to other existing categories. Thanks to the fulfillment of all this required process, it was possible to obtain the sanitary notification for fresh cheese, which guarantees its quality and safety, for this reason the University should encourage the productive area for people who have entrepreneurial ideas.